EFEK KEPUTUSAN PEMBELIAN MELALUI KUALITAS PELAYANAN, HARGA, CITA RASA DAN EXPERIENTIAL MARKETING - Romadhoni, Buyung; S.Themba, Orfyanny (Journal of Economic, Public, and Accounting (JEPA), 2023)
This research aims to influence service quality, price, taste and experiential marketing on purchasing decisions. This research is an associative research with a causal relationship. In this study, the population size was unknown and the researcher decided to use a sample of 100 respondents. The sample technique is purposive sampling with the respondent criteria from the sample being consumers who have visited and purchased products at Jalangkote Lasinrang Makassar. To examine the relationship between variables, this study used the SPSS program to perform multiple regression analysis. The results of the research found that service quality, price, taste and experiential marketing had a positive or significant effect on purchasing decisions at Jalangkote Lasinrang Makassar.